Cantor fractal-based printed slot antenna for dual-band wireless applications. Issue 2 (8th December 2014) - Ali, Jawad; Abdulkareem, Seevan; Hammoodi, Ali; Salim, Ali; Yassen, Mahmood; Hussan, Mohammed; Al-Rizzo, Hussain
Abstract : Fractal geometries are attractive for antenna designers seeking antennas with compact size and multiband resonant behavior. This paper presents the design of a new microstrip-fed printed slot antenna for use in dual-band wireless applications. The slot structure of the proposed antenna is in the form of Cantor square fractal geometry of the second iteration. The slot structure has been etched on the ground plane of a substrate with relative permittivity of 4.4 and 1.6 mm in thickness. A parametric study is conducted to explore the effects of some geometrical parameters on the antenna performance. Results show that the antenna possesses a dual-band behavior with a wide range of resonant frequency ratio. In addition to the ease of fabrication and simple design procedure, the antenna offers desirable radiation characteristics. A prototype of the proposed antenna has been simulated, fabricated, and measured. The measured 10 dB return loss bandwidths for the lower and the upper resonant bands are 42% (2.35–3.61 GHz) and 20% (5.15–6.25 GHz), respectively. This makes the proposed antenna suitable to cover a number of operating bands of wireless systems (2.4 GHz-Bluetooth, 2.4 GHz ISM, 2.4/5.8 GHz-WLAN, 3.5 GHz-WiMAX, and 5.8 GHz-ITS).